2003
DOI: 10.1149/1.1593041
|View full text |Cite
|
Sign up to set email alerts
|

A SECM Study of Heterogeneous Redox Activity at AA2024 Surfaces

Abstract: Scanning electrochemical microscopy ͑SECM͒ was used to spatially resolve the heterogeneous cathodic activity at AA2024 surfaces. Experiments used a 10 m diameter Pt microelectrode in a solution containing the protonated form of ͑dimethylamino͒ methylferrocene ͓DMAFc ϩ , i.e., the Fe͑II͒ state͔. The tip was brought near the alloy surface while held at a potential of 0.65 V vs. SCE, where DMAFc ϩ is oxidized to DMAFc 2ϩ ͓i.e., the Fe͑III͒ state͔. The AA2024 substrate was held at Ϫ0.75 V, where the DMAFc 2ϩ produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 30 publications
3
56
0
1
Order By: Relevance
“…EDX maps of an area imaged with SECM show that Cu-containing secondary phases are mainly responsible for this high electrochemical activity, while other elemental inclusions do not contribute to the positive feedback (Figure 27). This is in accordance with similar investigations by Seegmiller and Buttry [203] who have shown that copper inclusions are responsible for the presence of sites with high cathodic activity at the surface of the same Al alloy.…”
Section: Investigation Of Precursor Regionssupporting
confidence: 93%
See 1 more Smart Citation
“…EDX maps of an area imaged with SECM show that Cu-containing secondary phases are mainly responsible for this high electrochemical activity, while other elemental inclusions do not contribute to the positive feedback (Figure 27). This is in accordance with similar investigations by Seegmiller and Buttry [203] who have shown that copper inclusions are responsible for the presence of sites with high cathodic activity at the surface of the same Al alloy.…”
Section: Investigation Of Precursor Regionssupporting
confidence: 93%
“…It complements other scanning probe techniques such as the scanning reference electrode technique (SRET) [178,179], conductive scanning force microcopy (CSFM), electrochemical scanning tunneling microscopy (ECSTM), and scanning Kelvin probe techniques which are popular methods for the investigation of functional materials [180]. Basic experimental approaches include the imaging of the permeability of applied protective coatings [181][182][183][184][185][186][187][188][189][190][191][192][193], the imaging of regions with distinctly higher electron transfer rates which may be precursor sites for pitting corrosion [29,57,[194][195][196][197][198][199][200][201][202][203][204][205][206][207], the initiation of pitting corrosion by local generation of aggressive species at the UME [208,209] and the detection of active corrosion by collecting released species [55,58,60,104,[210][211][212][213][214]…”
Section: Localized Corrosionmentioning
confidence: 99%
“…It has been found that the local surface conditions affected the heterogeneous electrochemical behavior of the alloy. Seegmiller and Buttry [17] used the scanning electrochemical microscopy (SECM) to investigate the cathodic activity at AA2024-T3 surfaces which turned out more intense on the intermetallic particles present in the microstructure rather than on the aluminum matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring of active corrosion by SECM has been realized on a range of materials by identification of locally released species by cyclic voltammetry at the UME or by use of ion-selective potentiometric microelectrodes. The materials investigated include steel [100][101][102], dental fillings [103,104], Si [105], Ti [106,107], alloys [76,[108][109][110][111][112][113], ZnSe wave-guides [114], organic coatings on metallic substrates [115][116][117], AgI-based ion-selective membranes [118], and composite-based amperometric biosensors [119]. Simões et al [120] studied the corrosion behavior of an iron/zinc galvanic couple immersed in aqueous sodium chloride solution.…”
Section: Metalsmentioning
confidence: 99%